2008
DOI: 10.1016/j.chembiol.2008.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Dissection of the Natural Product Cyclopentapeptide Chitinase Inhibitor Argifin

Abstract: SummaryChitinase inhibitors have chemotherapeutic potential as fungicides, pesticides, and antiasthmatics. Argifin, a natural product cyclopentapeptide, competitively inhibits family 18 chitinases in the nanomolar to micromolar range and shows extensive substrate mimicry. In an attempt to map the active fragments of this large natural product, the cyclopentapeptide was progressively dissected down to four linear peptides and dimethylguanylurea, synthesized using a combination of solution and solid phase peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 40 publications
0
74
0
Order By: Relevance
“…Although Hajduk (8) did not show that the fragment positions are actually conserved, such data are available in a number of other studies. Andersen et al (9) shortened the natural cyclopentapeptide argifin, a chitinase inhibitor, to a series of dimethylguanyl-urea containing peptides and finally to dimethylguanyl-urea. The binding of fragments was analyzed by X-ray crystallography, and their conformations were shown to be similar to that observed in argifin.…”
mentioning
confidence: 99%
“…Although Hajduk (8) did not show that the fragment positions are actually conserved, such data are available in a number of other studies. Andersen et al (9) shortened the natural cyclopentapeptide argifin, a chitinase inhibitor, to a series of dimethylguanyl-urea containing peptides and finally to dimethylguanyl-urea. The binding of fragments was analyzed by X-ray crystallography, and their conformations were shown to be similar to that observed in argifin.…”
mentioning
confidence: 99%
“…Although a simple arginine-derived inhibitor 2 discovered by van Aalten and co-workers had been reported independently, 13 it showed low inhibitory activity against SmChi in contrast to argifin 1, which was examined by our group (Figure 2). We synthesized the azide-bearing inhibitor 3 as a reactive scaffold for capturing complementary acetylenic reagents to form triazole-linked inhibitors by TGS.…”
Section: Resultsmentioning
confidence: 84%
“…In fact, van Aalten and co-workers revealed through X-ray analysis that the ability of the N o -methylcarbamoyl group to penetrate fully into the active-site pocket of chitinases strongly correlated with the inhibition of chitin hydrolysis. 13 Hence, we concluded that the N o -methylcarbamoyl-L-arginine core represents an ideal anchor to derivatize and elaborate better chitinase inhibitors.…”
Section: Introductionmentioning
confidence: 90%
“…For example, the large and counterintuitive enthalpic penalty associated with ligand binding to subsites +2 and +3 needs to be taken into account in current efforts to design chitinase inhibitors [31].…”
Section: Resultsmentioning
confidence: 99%